Analisis Kadar Zat Besi (Fe) Serum dan Jumlah Eritrosit Remaja Putri Anemia yang Mendapatkan Program Makan Bergizi Gratis - Hendrawati T. Mou; Margaretha Solang; Vivien Novarina A. Kasim; Djuna Lamondo; Mustamin Ibrahin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Anemia is a condition when the hemoglobin (Hb) level in the blood is lower than the normal limit. Adolescent girls are at high risk of experiencing anemia due to regular blood loss during menstruation, and iron (Fe) deficiency is the main factor causing iron deficiency anemia, which is a condition resulting from insufficient iron for hemoglobin synthesis in erythrocytes that function to transport oxygen. The aim of this study is to determine the serum iron (Fe) levels and the number of erythrocytes in anemic adolescent girls who receive a free nutritious meal program. The research method used is an analytical observational approach with a cross-sectional design. The population in this study consisted of 80 anemic femal students, with a sample size of 40 anemic female students. The research results show that the iron levels in anemic adolescent girls who received the MBG program averaged 97.14 ± 91.67, and the average erythrocyte count was 4.87 ± 0.54. The results indicate that the average of both variables is still within the normal range. Meanwhile, the results in the group that has not received free nutrition show an average erythrocyte count of 4.73 ± 0.31, while the average iron level is at 47.50 ± 19.39.